A relação homem-natureza: um paralelo entre Espinosa e Feuerbach - Sousa, André Luís Bonfim (2009)
The aim of this work is to comprehend the relationship between Man and Nature in Espinosa and Feuerbach’s works. We did a parallel between the two philosophers, where we tried to make clear similarities and differences. The question of the relationship between man and nature is in the middle of Espinosa and Feuerbach philosophies. In both is clear the following notion: we can’t to know the nature without the man and we can’t to know the man without the nature. In this way, we tried to show one interesting man comprehension presented of Espinosa and Feuerbach. For one hand, this comprehension wants to know: what the man can? For other hand, it wants to give autonomy and dignity to Nature, considered by Espinosa and Feuerbach as the fundamental and cause of Man. With these questions, the word ends showing the importance of Espinosa and Feuerbach to resolve and comprehend the Modern and Contemporary questions, as ecological crisis, individualism and values fragmentation.